Psychological and Pedagogical Preconditions for Teaching Swimming to Primary School Children - Alina NINICU; Oana Verona NEUMANN; Oleg POSTOLACHI (ACROSS)
Swimming as a type of physical exercise is an almost ideal model for studying the problems of the theory of learning motor actions, as here we are dealing with the complete absence of any skill, such as the habit of moving in the water. According to some data, the formation of swimming skills depends on the level of development of motor skills. Children with a high level of motor skills control are more likely to outperform others in learning to swim. And in order to raise a child's genetic abilities, we need to know what those abilities are and how to develop them. The specificity of the aquatic environment leaves a significant imprint on the learning process, which may explain the large number of options in swimming learning schemes. A number of authors propose to use the form of the training game when teaching swimming. However, despite the huge number of methodological means and techniques used in teaching swimming, the possibilities of education for development, goal setting, propulsion systems, self-monitoring and self-assessment, i.e. what reflects the current state of teaching, are not yet sufficiently used.